(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Anemia is among the most important complications of chronic kidney disease (CKD) and a lot of symptoms and signs are due to this problem. Erythropoietin injection may improve anemia, but it may cause hypertension in these patients. The aim of this study is to evaluate erythropoietin injection effects on blood pressure of hemodialysis and predialysis patients. Materials and Methods. Forty hemodialysis patients and 40 predialysis patients with end-stage renal disease were enrolled in the study. The studied patients were comparable in terms of age, sex, hemoglobin, serum calcium, and baseline blood pressure. Erythropoietin was injected for all of the patients with anemia (4000 U, twice weekly). The effect of erythropoietin on their blood pressure was evaluated for each group by comparison of systolic, diastolic, and mean arterial blood pressure values before and 1 hour after the injection. Results. After erythropoietin injection, systolic, diastolic, and mean arterial blood pressure values increased significantly in the hemodialysis group, and the increases were significantly greater in this group than the predialysis group (P = .02, P = .01, and P = .02, respectively). Blood pressure increase was significant only for the systolic component in the predialysis group. Conclusions. Erythropoietin injection increases blood pressure levels in both groups. However, this is more significant in the hemodialysis patients as compared with patients with end-stage renal disease who have not started dialysis. Monitoring of blood pressure after erythropoietin injection is recommended.